Using a Discrete-Event System Specifications (DEVS) for designing a Modelica compiler. (January 2015) - Wainer, Gabriel A.; D'Abreu, Mariana C.
Highlights: Models can be defined in Modelica and are translated into DEVS models. An intermediate code generator transforms the models in Bond Graphs. We focus on the construction of the compiler, showing the different steps of the process. We show how to model these dynamic systems under the discrete event abstraction. We discuss different examples based on Modelica's electrical library. Abstract: We introduce a new architecture for the design of a tool for modeling and simulation of continuous and hybrid systems. The environment includes a compiler based on Modelica, a modular and a causal standard specification language for physical systems modeling (the tool supports models composed using certain component classes defined in the Modelica Standard Library, and the instantiation, parameterization and connection of these MSL components are described using a subset of Modelica). Models are defined in Modelica and are translated into DEVS models. DEVS theory (originally defined for modeling and simulation of discrete event systems) was extended in order to permit defining these of models. The different steps in the compiling process are show, including how to model these dynamic systems under the discrete event abstraction, including examples of model simulation with their execution results.